Geochemical diversity in first rocks examined by the Curiosity Rover in Gale Crater: Evidence for and significance of an alkali and volatile‐rich igneous source. Issue 1 (16th January 2014) - Schmidt, M. E.; Campbell, J. L.; Gellert, R.; Perrett, G. M.; Treiman, A. H.; Blaney, D. L.; Olilla, A.; Calef, F. J.; Edgar, L.; Elliott, B. E.; Grotzinger, J.; Hurowitz, J.; et al.
Abstract [1] The first four rocks examined by the Mars Science Laboratory Alpha Particle X‐ray Spectrometer indicate that Curiosity landed in a lithologically diverse region of Mars. These rocks, collectively dubbed the Bradbury assemblage, were studied along an eastward traverse (sols 46–102). Compositions range from Na‐ and Al‐rich mugearite Jake_Matijevic to Fe‐, Mg‐, and Zn‐rich alkali‐rich basalt/hawaiite Bathurst_Inlet and span nearly the entire range in FeO* and MnO of the data sets from previous Martian missions and Martian meteorites. The Bradbury assemblage is also enriched in K and moderately volatile metals (Zn and Ge). These elements do not correlate with Cl or S, suggesting that they are associated with the rocks themselves and not with salt‐rich coatings. Three out of the four Bradbury rocks plot along a line in elemental variation diagrams, suggesting mixing between Al‐rich and Fe‐rich components. ChemCam analyses give insight to their degree of chemical heterogeneity and grain size. Variations in trace elements detected by ChemCam suggest chemical weathering (Li) and concentration in mineral phases (e.g., Rb and Sr in feldspars). We interpret the Bradbury assemblage to be broadly volcanic and/or volcaniclastic, derived either from near the Gale crater rim and transported by the Peace Vallis fan network, or from a local volcanic source within Gale Crater. High Fe and Fe/Mn in Et_Then likely reflect secondary precipitation of Fe3+ oxides as a cement or rind. The K‐rich signature of the Bradbury assemblage, if igneous in origin, may have formed by small degrees of partial melting of metasomatized mantle.